A Rare Testicular Cancer, Adenocarcinoma of Rete Testis: A Case Report - Budaya, Taufiq Nur; Fabrianta, Dio Mafazi; Seputra, Kurnia Penta (International Journal of Psychosocial Rehabilitation, 2020)
Primary adenocarcinoma of rete testis is an extremely rare intrascrotal neoplasm occurring most frequently in elderly males but has a wide age range of 8-91 years. Although near about 60 cases of rete testis carcinoma have been published till date, less than 30 cases had fulfilled the strict diagnostic criteria required for true rete testis adenocarcinoma. A 32-year-old male was admitted with complaints of swelling and pain in left side of the scrotum since 1 year ago. Physical examination revealed a giant swelling of the left scrotum. Laboratory findings showed elevation of α-fetoprotein (AFP) with level of >1210 ng/ml and β‐human chorionic gonadotropin (β-HCG) with level of 15739 mIU/ml. Chest X-Ray showed a suspected of a metastatic nodule in the lung. Left inguinal orchiectomy was performed. Pathological examination demonstrated that the edge of the incision and spermatic chord was free of tumor. The histopathological conclusion was adenocarcinoma. 3 months after the operation AFP level fell to 203,2 ng/ml, the β-HCG fell to 3732 mIU/ml, and the LDH level was 788 U/L. 5 months after the operation CT-Scan showed that there was a recidive mass in the projection of left testicle, multiple para-aortic lymphadenopathy, and multiple metastatic nodes in the both side of the lung alongside with elevated levels of AFP (7978 ng/ml) and β-HCG (21866 mIU/ml). The therapy continued with 4 series BEP Chemotherapy. Adenocarcinoma of the rete testis is an extremely rare tumor type with a poor prognosis.